Morphological variation in the genus Juliomys (Rodentia: Cricetidae: Sigmodontinae) and taxonomic status of Juliomys anoblepas (Winge 1887) from the Quaternary of Southeast Brazil - Pires, Carolina; Weksler, Marcelo; Bonvicino, Cibele R. (Zootaxa, 2020)
The region of Lagoa Santa, Minas Gerais, Brazil, is one of the most important karstic areas of the Brazilian Quaternary due to the faunistic diversity of living and extinct forms. Among them, some taxa remain poorly studied, as is the case of Calomys anoblepas Winge 1887. Despite the recent allocation of the taxon within Juliomys, its description and morphological analysis are condensed, based on comparative few specimens and on few informative characters. In this study, we investigate characters proposed to distinguish species of Juliomys, and reevaluate the taxonomic status of the fossil Juliomys anoblepas. We analyzed 80 cranio-dental morphological characters in 233 specimens represented by the four species currently recognized: J. pictipes (Osgood 1933), J. rimofrons Oliveira & Bonvicino 2002, J. ossitenuis Costa, Pavan, Leite & Fagundes 2007, and J. ximenezi Christoff, Vieira, Oliveira, Gonçalves, Valiati & Tomasi 2016. We also performed principal component analysis on eight craniodental measurements available for the J. anoblepas hypodigm. The review of morphological systems and the evaluation of the characters used in the literature revealed that there are no diagnostic characters in the anterior portion of the skull and in the molar series of Juliomys, being difficult to differentiate the fossil from the other living species. Only six qualitative characters were variable and applicable to the hypodigm of J. anoblepas. Characters are polymorphic, invariable, or the fossil is not sufficiently complete to determinate its states. The taxon could not be morphometrically differentiated from J. pictipes and J. ossitenuis. Based on the results presented herein, we consider J. anoblepas as a nomen dubium and restrict its name to the taxon’s hypodigm.